(untitled) (Global Journal of Science Frontier Research, 2019)
The present study was conducted around the ash disposal sites of Ramagundam Super thermal power Plant (TPPs) Surrounding agricultural lands. It is situated in Peddapalli Telangana. Fly ash is produced as a result of coal combustion in thermal power station and discharged in ash ponds. Basically the releasing of huge amount of flay ash affects the soil quality. Detected higher concentration of Ca, Mg, Na, K and many more element in the sample of some sites while recorded minimum concentration in some site in all the collected samples.